The role of green human resource management in driving hotel's environmental performance: Interaction and mediation analysis. (July 2020) - Pham, Nhat Tan; Vo Thanh, Tan; Tučková, Zuzana; Thuy, Vo Thi Ngoc
Graphical abstract: Highlights: The indirect and interactive effects of GHRM practices on environmental performance. Interaction of training and employee involvement affects environmental performance. OCBE mediates effects of training and performance management on environmental performance. This study is the first to examine these effects in the hotel industry. Abstract: Previous studies have paid little attention to the links between green human resource management (GHRM) and environmental performance, especially examining an interaction and mediation analysis in the hospitality management. Therefore, the study bridges this research gap by extending the Ability-Motivation-Opportunity theory to explore the direct, indirect, and interactive roles of GHRM practices. A survey of 220 respondents at hotels suggests that: (1) training and employee involvement are critical tools in directly stimulating employee commitment and organisational citizenship behaviour towards the environment (OCBE), and hotels' environmental performance; (2) OCBE plays an essential role in mediating the effects of training and performance management on environmental performance; and (3) the vital interaction of training and employee involvement significantly strengthens environmental performance. However, unexpected results are found: (1) performance management is an unimportant consideration in analysis of direct and interactive influences and (2) employee environmental commitment does not mediate the GHRM-environmental performance relationship.